Violent Distortions: Bearing Witness to the Task of Wartime Translators - Stahuljak, Zrinka (TTR)

(untitled) (Association canadienne de traductologie, 2000)
AbstractViolent Distortions: Bearing Witness to the Task of Wartime Translators — By using the example of translators during the 1991-1992 war in Croatia, this article addresses the position of the translator in war in order to rethink the foundations of the metaphorical relationship between testimony and translation. If the theories of testimony do not allow the translator the position of a witness, how can then translation be "une métaphore de tout témoignage"? Taking the problem of distortion in translation, the author demonstrates how the failure to translate emerges as the testimony of the translator, one which, moreover, negates the metaphorical link of testimony and translation. The article concludes by showing how the translator as a witness is also excluded from the theory of translation.